Proceedings of the 8th Workshop on Parallel and Distributed Systems: Testing, Analysis, and Debugging 2010
DOI: 10.1145/1866210.1866215
|View full text |Cite
|
Sign up to set email alerts
|

A platform for search-based testing of concurrent software

Abstract: The paper describes a generic, open-source infrastructure called SearchBestie (or S'Bestie for short) that we propose as a platform for experimenting with search-based techniques and for applying them in the area of software testing. Further, motivated by a lack of work on search-based testing targeted at identifying concurrency-related problems, we instantiate S'Bestie for search-based testing of concurrent programs using the IBM's concurrency testing infrastructure called ConTest. We demonstrate on series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…We used these controls because previous work indicates that they can impact the effectiveness of the testing process [13]. The specific values used were selected based on our previous experience in this domain [15] and pilot studies, both of which indicated that larger or finer grained delays and probabilities did not yield significantly different results.…”
Section: ) Test Generation and Executionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used these controls because previous work indicates that they can impact the effectiveness of the testing process [13]. The specific values used were selected based on our previous experience in this domain [15] and pilot studies, both of which indicated that larger or finer grained delays and probabilities did not yield significantly different results.…”
Section: ) Test Generation and Executionmentioning
confidence: 99%
“…Thus, to maximize the effectiveness of testing processes, researchers create test adequacy criteria based on these metrics, and develop techniques to quickly satisfy them. The development of such techniques has long been an active area of research in the context of structural coverage metrics for non-concurrent programs [8], [9], [10], [11], and as multithreaded programs have become more common the development of techniques centered around concurrent coverage metrics has also become an active area of research [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is motivated by the rise of multicore systems [Sutter and Larus 2005], the ineffectiveness of traditional testing for detecting and reproducing concurrency bugs due to nondeterminism [Křena et al 2010], and the desire for automatic, precise analysis, which is hard to achieve using static techniques [Bessey et al 2010]. …”
Section: Introductionmentioning
confidence: 99%
“…There are only few approaches that try to generate not only schedules, but also test cases: Krena et al [13] proposed a search-based technique that optimizes schedules used by the Contest [7] tool. Ballerina [19] uses random test prefixes, and then explores two methods executed in parallel in two different threads.…”
Section: B Concurrent Testingmentioning
confidence: 99%